Low tungsten content of nanostructured material supported on carbon for the degradation of phenol - Assumpção, M. H M T; De Souza, R. F B; Reis, R. M.; Rocha, R. S.; Steter, J. R.; Hammer, Peter [UNESP]; Gaubeur, I.; Calegaro, M. L.; Lanza, M. R V; Santos, Mirian Cristina dos [UNESP] (Elsevier, 2013)
A comparative study using different mass proportions of WO3/C (1%, 5%, 10% and 15%) for H2O2 electrogeneration and subsequent phenol degradation was performed. To include the influence of the carbon substrate and the preparation methods, all synthesis parameters were evaluated. The WO3/C materials were prepared by a modified polymeric precursor method (PPM) and the sol-gel method (SGM) on Vulcan XC 72R and Printex L6 carbon supports, verifying the most efficient metal/carbon proportion. The materials were physically characterized by X-ray diffraction (XRD) and by X-ray photoelectron spectroscopy (XPS) techniques. The XRD and the XPS techniques identified just one phase containing WO3 and elevated oxygen concentration on carbon with the presence of WO3. The oxygen reduction reaction (ORR), studied by the rotating ring-disk electrode technique, showed that WO3/C material with the lowest tungsten content (1% WO3/C), supported on Vulcan XC 72R and prepared by SGM, was the most promising electrocatalyst for H2O2 electrogeneration. This material was then analyzed using a gas diffusion electrode (GDE) and 585mgL-1 of H2O2 was produced in acid media. This GDE was employed as a working electrode in an electrochemical cell to promote phenol degradation by an advanced oxidative process. The most efficient method applied was the photo-electro-Fenton; this method allowed for 65% degradation and 11% mineralization of phenol during a 2-h period. Following 12h of exhaustive electrolysis using the photo-electro-Fenton method, the total degradation of phenol was observed after 4h and the mineralization of phenol approached 75% after 12h. © 2013 Elsevier B.V.
Keywords: Hydrogen peroxide electrogeneration; Phenol degradation; Tungsten oxide; Degradation of phenols; Electrogeneration; Gas diffusion electrodes; Oxygen reduction reaction; Polymeric precursor methods; Rotating ring-disk electrode techniques; Carbon; Electrocatalysts; Electrolytic reduction; Mineralogy; Phenols; Photoelectrons; Sol-gel process; Synthesis (chemical); Tungsten; X ray diffraction; X ray photoelectron spectroscopy; Biodegradation